Challenges in the management of severe allergic asthma in the elderly - Ozturk, Ayse Bilge (J Asthma Allergy, 2016)
Little is known about the features of asthma and allergy in the elderly. A significant number of elderly patients with asthma have uncontrolled and severe asthma. This review aims to provide an analysis of the literature on the assessment and phenotype of severe allergic asthma in the elderly. Gaps and pitfalls in diagnostic and therapeutic approaches, as well as management of severe allergic asthma in the elderly, are also discussed.